2021
DOI: 10.3389/fonc.2021.657876
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA LINC01929 Accelerates Progression of Oral Squamous Cell Carcinoma by Targeting the miR-137-3p/FOXC1 Axis

Abstract: Recently, additional long noncoding RNAs (lncRNAs) have been identified and their possible roles were investigated in a variety of human tumors. One of these lncRNAs, LINC01929, promoted the progression of some cancers, whereas its expression and biological function in human oral squamous cell carcinoma (OSCC) remains still mostly uncertain. The LINC01929 expression in OSCC tissues or cell lines was identified via quantitative real-time polymerase chain reaction. The cell counting kit-8, transwell migration, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…High LINC01614 expression was also markedly associated with the epithelial-mesenchymal transition (EMT), in uencing metastasis and the prognosis of several cancers 56 .LncRNA LINC02446 suppresses the proliferation and metastasis of bladder cancer cells by binding with EIF3G and regulating the mTORsignaling pathway 57 . Results from a related study suggest that TFAP2A-AS1 acts as a tumour suppressor in BC via the miR-933/SMAD2 axis 58 .lncLINC01929 accelerates the progression of oral squamous cell carcinoma by targeting the miR-137-3p/FOXC1 axis and is associated with survival in the TCGA dataset [59][60][61] . The high expression of KLHDC7B-DT aggravates pancreatic ductal adenocarcinoma development via inducing cross-talk between cancer cells and macrophages 62 .…”
Section: Discussionmentioning
confidence: 98%
“…High LINC01614 expression was also markedly associated with the epithelial-mesenchymal transition (EMT), in uencing metastasis and the prognosis of several cancers 56 .LncRNA LINC02446 suppresses the proliferation and metastasis of bladder cancer cells by binding with EIF3G and regulating the mTORsignaling pathway 57 . Results from a related study suggest that TFAP2A-AS1 acts as a tumour suppressor in BC via the miR-933/SMAD2 axis 58 .lncLINC01929 accelerates the progression of oral squamous cell carcinoma by targeting the miR-137-3p/FOXC1 axis and is associated with survival in the TCGA dataset [59][60][61] . The high expression of KLHDC7B-DT aggravates pancreatic ductal adenocarcinoma development via inducing cross-talk between cancer cells and macrophages 62 .…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of LINC01929 and ADAMTS12 enhanced cell invasion, while overexpression of miR-6785-5p had the opposite effect. lncRNA function may depend on its downstream binding molecules, such as ceRNA, which can regulate changes in target mRNA expression by competitively binding miRNA ( 50 ). In gastric cancer, lncRNA MT1JP binds miR-92a-3p to regulate FBXW7 expression, which in turn affects gastric cancer progression ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, among 14 prognostic lncRNAs, the function AC002546.1, AC010503.4, AC092142.1, AC092718.4, AL031316.1, AL136084.3 and U62317.1 have not been previously explored in breast cancer or other cancers. LINC01929 has been found positively correlated with tumor progression in liver cancer, oral squamous cell carcinoma and lung cancer[ 23 , 24 , 25 ]. Che et al indicated that LINC01929 promotes tumor progression through miR-137-3p/FOXC1 axis in oral squamous cell carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%